Creating Frustrated Lewis Pairs in Defective Boron Carbon Nitride for Electrocatalytic Nitrogen Reduction to Ammonia. Issue 36 (26th July 2022) - Lin, Wenwen; Chen, Hao; Lin, Gaobo; Yao, Siyu; Zhang, Zihao; Qi, Jizhen; Jing, Meizan; Song, Weiyu; Li, Jing; Liu, Xi; Fu, Jie; Dai, Sheng
Abstract: The electrocatalytic nitrogen reduction reaction (NRR) on metal‐free catalysts is an attractive alternative to the industrial Haber–Bosch process. However, the state‐of‐the‐art metal‐free electrocatalysts still suffer from low Faraday efficiencies and low ammonia yields. Herein, we present a molecular design strategy to develop a defective boron carbon nitride (BCN) catalyst with the abundant unsaturated B and N atoms as Lewis acid and base sites, which upgrades the catalyst from a single "Lewis acid catalysis" to "frustrated Lewis pairs (FLPs) catalysis." 14 N2 / 15 N2 exchange experiments and density functional theory (DFT) calculations reveal that FLPs can adsorb an N2 molecule to form a six‐membered ring intermediate, which enables the cleavage of N2 via a pull–pull effect, thereby significantly reducing the energy barrier to −0.28 eV. Impressively, BCN achieves a high Faraday efficiency of 18.9 %, an ammonia yield of 20.9 μg h −1  mg −1 cat., and long‐term durability. Abstract : Defect‐controlled boron carbon nitride (BCN) is synthesized with electron‐deficient B atoms and electron‐rich N atoms in defects, forming frustrated Lewis pairs (FLP) to promote the electrocatalytic N2 reduction to ammonia.